Comparison of haemodynamic responses in normotensive and hypertensive patients among three intubation devices: macintosh laryngoscope, intubating laryngeal mask airway and lightwand - Gvalani, S. K.; Mane, Sushant (International Journal of Research in Medical Sciences, 2016)
Background: The pressor response to endotracheal intubation is of special concern, especially in the presence of comorbidities like diabetes, hypertension, obesity and ischemic heart disease (IHD). It is commonly assumed that insertion of laryngeal mask airway (LMA) is associated with lesser hemodynamic fluctuations than conventional laryngoscopy. Also, the lightwand (LW) is believed to provoke a milder pressor response as it does not involve elevation of epiglottis. We decided to evaluate the pressor response to all three devices in normotensive and hypertensive patients. Methods: We conducted a randomized prospective study consisting of 126 patients posted for surgical procedures under general anesthesia. 63 hypertensive and 63 normotensive patients were randomly assigned to each intubation device: the macintosh laryngoscope (LS), the lightwand (LW), and the intubating laryngeal mask airway (ILMA).The peri-intubation hemodynamic parameters were recorded. Statistical analysis was done with SPSS version 17.0 Inter- and intra-group differences among the hemodynamic variables recorded over time were analyzed by using one-way analysis of variance for repeated measures with bonferroni post-test analysis as appropriate. All quantitative data were expressed as mean±standard deviation (SD). A p-value less than 0.05 was considered statistically significant. Results: All 3 devices (LS, ILMA and LW) are comparable with respect to hemodynamic fluctuations in normotensive patients. However, in hypertensive patients conventional laryngoscopy was associated with greater hemodynamic fluctuations than ILMA or LW. However there was no significant difference in the hemodynamic fluctuations between ILMA and LW. Conclusions: The ILMA and LW may be preferable to LS in hypertensive patients where attenuation of hemodynamic stress response is desired.